Detection of vulnerable atherosclerotic plaque during thoracic endovascular aortic repair using nonobstructive angioscopy. Issue 3 (March 2018) - Murakami, Takashi; Komatsu, Sei; Kodama, Kazuhisa; Shibata, Toshihiko
An angioscope was used to observe the intima of the aorta in an 82-year-old patient who had undergone thoracic endovascular aortic repair. The aortic angioscopic findings showed vulnerable plaques from the ascending aorta to the aortic arch that had not been visualized using preoperative computed tomography. After deploying a stent graft from zone 1 to zone 4, the proximal edge of the stent graft was adjacent to the ruptured plaque with mixed thrombi. In spite of these findings, the patient had an uneventful recovery. Angioscopy may have the potential to stratify the risk of thoracic endovascular aortic repair-related complications.